MARKET OF AGRICULTURAL LANDS IN THE PRESENT CONDITIONS - Shpik Н.; Smoliarchuk М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
It is worth reminding that since July 1, 2021, the government has lifted the ban on purchasing and selling of private agricultural lands to run commercial agricultural production, and land plots intended for private farming by the owners of land shares. It is proposed to study analytical information on the results of land relations in conditions of the open land market, starting from July 1, 2021. The work mentions about the number of completed agreements on purchase and sale of agricultural lands with the specified indicators, as well as outlines the dynamics of weighted average price of land intended for commercial agricultural production and private farming. The authors of the article describe regions characterized by the most active land market under martial law that is assessed by the indicators of completed agreements and the land area. The research also studies dynamics of the prices of purchase and sale of agricultural land since July 2021 to April 2023. A particular attention is also paid to electronic land auctions, which are considered a reference point of the fair price of land and the source of revenues to local budgets. The article names categories of the most promising buyers of agricultural lands and their opportunity to get a land plot. To provide the most complete information for the land market participants, the authors of the research outline the land market conditions, particularly who can buy land and what area, how the payments related with the land plots are made. The article also includes a list of documents, required for purchase and sale of land. In that context it is necessary to describe powers of communities (ATC) as to management of the land plots which are subject to purchase or sale.